2014
DOI: 10.1002/cbic.201402026
|View full text |Cite
|
Sign up to set email alerts
|

The Multivalent Effect in Glycosidase Inhibition: A New, Rapidly Emerging Topic in Glycoscience

Abstract: A bunch of keys, one lock: The multivalent effect in glycosidase inhibition is a new, rapidly emerging area with exciting potential and scope. This review presents a description of the different types of neoglycoclusters and their evaluation as glycosidase inhibitors. The first promising therapeutic applications are discussed, as well as the mechanisms underlying the observed inhibitory multivalent effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
71
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 127 publications
2
71
0
1
Order By: Relevance
“…[13][14] In the case of carbonic anhydrase, only studies on bivalent inhibitors were recently reported.I ndeed, Whiteside'sr esearch group describedi n2 012 the binding of monovalent and bivalent benzene sulfonamide ligandst oasynthetic dimer of carbonic anhydrase.…”
mentioning
confidence: 99%
“…[13][14] In the case of carbonic anhydrase, only studies on bivalent inhibitors were recently reported.I ndeed, Whiteside'sr esearch group describedi n2 012 the binding of monovalent and bivalent benzene sulfonamide ligandst oasynthetic dimer of carbonic anhydrase.…”
mentioning
confidence: 99%
“…In addition, this fluorophore was chosen for its biological/chemical stability and its photophysical properties including high extinction coefficient with reliable fluorescence [5455]. Another interest of the pyrene scaffold lies in its rigidity, a property that may favourably impact inhibitory multivalent effects [9,11,16,19]. A convergent approach comprising the attachment of azide-armed iminosugars 4 [1112] on polyalkyne “clickable” scaffolds 5 and 6 via Cu(I)-catalyzed azide–alkyne cycloaddition (CuAAC) was performed for achieving our synthetic goals (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1) [1,68]. Despite their high therapeutic potential, the extensive studies in the field and the myriad of compounds synthesized, very few examples of multivalent iminosugars were reported in the literature until recently [910]. From 2010, the field has however experienced a major take-off with the discovery of the first strong multivalent effects in glycosidase inhibition observed with DNJ clusters based on β-cyclodextrin or C 60 cores showing strong affinity enhancements over the corresponding monomers (up to 610-fold per DNJ unit) [1112].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term ''multivalent effect'', generally only employed with carbohydrate-binding proteins, could then be applied to the field of carbohydrate-processing enzymes. After this groundbreaking result, considerable amount of research has been reported, although almost exclusively with carbohydrate-processing enzymes such as glycosidases [34][35][36][37][38][39][40][41][42] and glycosyltranferases 43 . In a recent work, we reported the inhibitory study of coumarinderivatized fullerene hexakis-adducts toward a set of biologically relevant hCA isoforms 44 .…”
Section: Introductionmentioning
confidence: 99%